IMPACT OF COVID-19 AND JUNGLE CAT PREDATION ON RURAL POULTRY FARMING IN BELUN, WEST BENGAL, INDIA - CHOUDHURY, TANIMA; GHORAI, NARAYAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Covid-19 pandemic caused 61% reduction in the yearly income of the villagers. In order to makeup the income deficit the villagers increased the number of poultry birds they kept. The potential income from rural poultry farming for the year 2020 was INR 654000. The potential income from rural poultry farming for year 2021 could be INR 977250. This could lead to 49% increase in the potential income obtained from rural poultry farming. The jungle cats caused an economic loss of INR 188820. The jungle cats caused a decrease of 29% in the potential income that could have been obtained from rural poultry farming.